Remdesivir-Loaded Nanoliposomes Stabilized by Chitosan/Hyaluronic Acid Film with a Potential Application in the Treatment of Coronavirus Infection - Viktoria Milkova; Neli Vilhelmova-Ilieva; Anna Gyurova; Kamelia Kamburova; Ivaylo Dimitrov; Elina Tsvetanova; Almira Georgieva; Milka Mileva (MDPI AG, 2023)
An object of the present study was the development of liposomes loaded with the medicine Veklury® (remdesivir) stabilized by electrostatic adsorption of polysaccharide film formed from chitosans with different physicochemical characteristics and hyaluronic acid. The functionalization of the structures was achieved through the inclusion of an aptamer (oligonucleotide sequence) with specific affinity to the spike protein of the human coronavirus HCoV-OC43. The hydrodynamic size, electrokinetic potential and stability of the structures were evaluated at each step in the procedure. The encapsulation efficiency and loaded amount of remdesivir (99% and 299 µg/mL) were estimated by UV-vis spectroscopy. Our investigations showed manifestation of promising tendencies for prolonged periods of the drug release and increased effectiveness of its antiviral action. Among all studied versions of the delivery system, the most distinguished and suitable in a model coronavirus therapy are the liposomes formed from chitosan oligosaccharides. The cytotoxicity of the liposomes was determined against the HCT-8 cell line. A cytopathic effect inhibition test was used for the assessment of the antiviral activity of the compounds. The virucidal activity and the effect on the viral adsorption of the samples were reported by the end-point dilution method, and the alteration in viral titer was determined as Δlgs compared to untreated controls. The redox-modulating properties of the nanoparticles were studied in vitro in certain/several/a few chemical model systems. Our investigations showed a manifestation of promising tendencies for a prolonged effect of the drug release and increased effectiveness of its antiviral action.